Cake and confessions - Remington, Laurel (Sourcebooks Jabberwocky, 2019)
Twelve-year-old Scarlett's wildly successful blog may lead to a television show, the Secret Cooking Club has new members, and she is going to bake her mother's wedding cake, but trouble is looming.